Changing Climate, Changing Food Consumption? Impact of Weather Shocks on Nutrition in Malawi. - McLaughlin, Shannon Marie; Bozzola, Martina; Nugent, Anne (Journal of Development Studies, 2023)
In this study, we capture the impact of changing temperature and rainfall patterns on the estimated consumption of macro-and micronutrients among households in Malawi. We apply a fixed-effects model to household panel data collected between 2010 and 2017, which contains detailed information on food consumption, combined with rainfall and temperature data over the past 30 years. In turn, we aim to identify the impact of weather shocks on household food and nutrition security. We find decreases in rainfall from the long-term average results in declining daily consumption of macronutrients (carbohydrates, protein, fat), and micronutrients (iron, zinc, vitamin C, and B2). Increases in temperature from the long-term average are associated with reduced daily consumption of carbohydrates, protein, iron, zinc, vitamin A, B2, folate, and B12. These results suggest that reduced rainfall and higher temperatures will exacerbate food insecurity in Malawi. As the effects of climate change are becoming more apparent, enhancing our understanding of the effect of weather shocks on nutrition in developing countries will be vital to aid policymakers to implement targeted interventions to advance food and nutrition security in Sub-Saharan Africa. This will be essential to achieve the sustainable development goal of 'Zero Hunger' by 2030.